Information systems project management - Avison, D. E.; Torkzadeh, Gholamreza; Sage eBooks (Los Angeles ; London : SAGE, 2009)
'Information Systems Project Managemet' reflects new thinking about the need for balance between technology topics and production-operations issues needed to manage successful information systems projects.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Information resources management; Information technology -- Management; Project management; Electronic books